Long-term variabilities in thermal structure, CO2 concentration and associated cooling rates in the Earth's middle atmosphere: Observations and model simulations. (May 2023) - Pramitha, M.; Kishore Kumar, K.; Praveen, M.
Abstract: Enhanced anthropogenic activities in the recent decades are ensuing in the large-scale accumulation of carbon dioxide (CO2 ) concentration in the Earth's atmosphere. CO2 in the atmosphere induces warming in the troposphere and cooling in the middle atmosphere. A systematic analysis of the middle atmospheric thermal structure and its variability at decadal scale is need of the hour to perceive the consequences of increased anthropogenic activity in totality. In this regard, long-term variations of temperature, CO2 concentration and associated cooling rates in the middle and upper atmosphere (30–110 km) are investigated using Sounding of Atmosphere by Broadband Emission Radiometry (SABER) on board Thermosphere, Ionosphere, Mesosphere Energetics and Dynamics (TIMED) satellite observations during 2002–2021 and Specified Dynamics-Whole Atmosphere Community Climate Model (SD-WACCM) simulations during 2002–2017 over 50 N–50 S latitudes. The results show that CO2 concentration measured by SABER is significantly underestimated by the WACCM simulations, especially above 90 km altitude. In order to find the long-term trends in each variable, Multivariate Linear Regression (MLR) technique is employed to the residual data obtained after removing seasonal variations. SABER observations show decreasing trend in temperature with a rate of 0.5–2.5 K/decade and an increase in CO2 vmr of 16–18 ppmv/decade. The effect of Solar Cycle, QBO and ENSO on each of the variables is also investigated. The significance of the present study lies in evaluating the SD-WACCM simulations of long-term variabilities in the thermal structure, CO2 vmr and associated cooling rates using two decades of observations. Highlights: Long term trends in middle atmospheric temperature, CO2 vmr and cooling rates from SD-WACCM are evaluated using SABER observations. Response of middle atmospheric temperature, CO2 vmr and associated cooling rates to solar cycle, QBO, ENSO is investigated. Observations show a decreasing trend in temperature at a rate of 0.5–2.5 K/decade in the middle atmosphere.